2014
DOI: 10.1007/s11920-014-0498-0
|View full text |Cite
|
Sign up to set email alerts
|

Use of EEG to Diagnose ADHD

Abstract: Electroencephalography (EEG) has, historically, played a focal role in the assessment of neural function in children with attention deficit hyperactivity disorder (ADHD). We review here the most recent developments in the utility of EEG in the diagnosis of ADHD, with emphasis on the most commonly used and emerging EEG metrics and their reliability in diagnostic classification. Considering the clinical heterogeneity of ADHD and the complexity of information available from the EEG signals, we suggest that consid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
146
3
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 220 publications
(152 citation statements)
references
References 89 publications
(101 reference statements)
1
146
3
2
Order By: Relevance
“…Research on theta/beta has been dominated by investigations of its diagnostic value, which, to date, has yielded mixed evidence. Some studies have shown that high theta/beta is predictive of ADHD (Monastra, Linden, Lubar, & Vandeusen, 1999) whereas others have not (Ogrim, Kropotov, & Hestad, 2012; for excellent reviews, see Arns, Conners, & Kraemer, 2011;Barry, Clarke, & Johnstone, 2003;Lenartowicz & Loo, 2014;Loo et al, 2012). A series of studies by Shutter and colleagues have shown that theta/beta is associated with executive control processes.…”
Section: Theta/beta and Executive Functionmentioning
confidence: 99%
“…Research on theta/beta has been dominated by investigations of its diagnostic value, which, to date, has yielded mixed evidence. Some studies have shown that high theta/beta is predictive of ADHD (Monastra, Linden, Lubar, & Vandeusen, 1999) whereas others have not (Ogrim, Kropotov, & Hestad, 2012; for excellent reviews, see Arns, Conners, & Kraemer, 2011;Barry, Clarke, & Johnstone, 2003;Lenartowicz & Loo, 2014;Loo et al, 2012). A series of studies by Shutter and colleagues have shown that theta/beta is associated with executive control processes.…”
Section: Theta/beta and Executive Functionmentioning
confidence: 99%
“…Collectively, this broader focus on etiologic and symptomatic heterogeneity within psychiatric disorders and new focus on examination of domains of function across disorders has implications for efforts to develop more robust, highly cost effective EEG‐based biomarkers for psychiatric disorders. It seems unlikely that a single biomarker measure of any type can capture all of the variance within a diagnostic category (Lenartowicz & Loo, ). Instead, finding biomarkers for neural circuits associated with domains of functioning that are abnormal across several disorders seems a potentially more fruitful approach.…”
Section: Shift To Shared Genetic and Mechanistic Factors Across Disormentioning
confidence: 99%
“…In brief, studies at the end of the 1990s through 2009 have reported a higher TBR among children and adolescents with ADHD compared to non‐ADHD groups, with overall large effect sizes (ES) of 1 Standard Deviation or greater. Since 2009, however, several independent research groups have reported findings that have contradicted these earlier TBR‐ADHD results (Lenartowicz & Loo, ). Effect sizes have diminished significantly over the past 6 years, with a highly significant correlation between effect size and year of publication (Pearson r = −.97) emerging in a meta‐analysis by Arns et al.…”
Section: The Theta/beta Ratio and Adhd Diagnosismentioning
confidence: 94%
“…The TBR is a ratio of spectral power in the theta frequency band (4–7 Hz) relative to power in the faster, beta frequency band (13–21 Hz), which is sometimes measured at a single electrode site (Cz) during rest. This measure has often been investigated in ADHD samples, with widely disparate findings depending on the publication date of the study (see Arns, Conners, & Kraemer, ; Lenartowicz & Loo, , for review). In brief, studies at the end of the 1990s through 2009 have reported a higher TBR among children and adolescents with ADHD compared to non‐ADHD groups, with overall large effect sizes (ES) of 1 Standard Deviation or greater.…”
Section: The Theta/beta Ratio and Adhd Diagnosismentioning
confidence: 99%